Achieving excellent dielectric performance in polymer composites with ultralow filler loadings via constructing hollow-structured filler frameworks. (April 2020) - Yang, Jie; Zhu, Xiaotong; Wang, Huanlei; Wang, Xin; Hao, Chuncheng; Fan, Runhua; Dastan, Davoud; Shi, Zhicheng
Abstract: Dielectric polymer composites are promising candidates for pulsed power capacitors. Enhanced dielectric performance is usually achieved at the expense of high filler loadings. Herein, we report the realization of significantly enhanced dielectric performances in epoxy composites with ultralow BaTiO3 loadings via constructing hollow-structured BaTiO3 frameworks with hierarchical interfaces in epoxy. An enhanced dielectric permittivity of 22 @10 kHz, which is about 5 times that of the epoxy matrix, is achieved in the composite with merely 5 vol% BaTiO3, while the dielectric loss keeps low (tanδ ≈ 0.032 @10 kHz). Meanwhile, a greatly improved energy density which is about 250% that of the epoxy matrix and a high discharge efficiency ( η  = 89.7%) are achieved simultaneously. It is believed that, the hollow-structured BaTiO3 frameworks with hierarchical interfaces leads to strengthened interfacial polarization and ensures continuous transmission of polarization, which collectively improve the dielectric energy-storage performance.